Family Conflict Resolution Through Mediation In Indonesia And Malaysia: A Sociological Study Of Islamic Law - Any Ismayawati; Aristoni; Syed Mohammad Chaedar Syed Abdurrahman Al Yahya (Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2025)
Index (Tier 2)